Exploring the mental health and wellbeing of professional academy footballers in England - Sothern, N. A.; O'Gorman, J. (Soccer & Society, 2021)
The mental health and wellbeing of elite footballers is beginning to receive much needed attention in research and practice terms. However, to date much of the knowledge generated and initiatives designed to improve provision for elite footballers` mental health and wellbeing is centred on adults. The mental health and wellbeing of junior footballers attached to elite development programmes have largely been overlooked. In England, this is particularly concerning given an estimated 12,500 young professional academy footballers are attached to such systems. Semi structured interviews were conducted to explore the extent to which social ties and interactions with significant others shaped the mental health and wellbeing of twelve professional academy footballers based in four category one football academies in England . Drawing on concepts derieved from symbolic interactionism, the analysis of the findings highlighted; i) the demands and expectations of their role often negatively affected emotions, ii) concealment of mental health and wellbeing issues to significant others in primary and secondary social networks, and ii) portrayals of the self-intended to foster positive relations with significant others to avoid stigmatization. Future research and practice should seek to inform and promote more effective interventions and models that more adequately support the mental health and wellbeing of professional academy footballers.